(NwYRAZITELXNYE SREDSTWA LIRIKI ~AJKOWSKOGO(B.s (NmONOGRAFIQs - (Nw(B. (NcUKKERMANs ((NmOSKWAs (NmUZYKAs, 1971)
(NzAGLAWIE \TOJ KNIGI DUMAETSQ UVE DOLVNO DATX ^ITATEL@ PERWONA^ALXNOE PREDSTWLENIE O EE SODERVANII(B.s